Cuestiones y criterios de la traducción gallega del Canzoniere: su papel en la conformación del canon poético en Galicia - Rodríguez Barcia, Moisés; Pedreira Rodríguez, Penélope (Cuadernos de Filología Italiana, 2005)
The Galician literature does not rely on poets like Camões, Garcilaso or Ronsard, and this lack was not corrected even by the translations of the epoch, since the Italian classic authors did not start being translated into the Galician until up to the decade of 1980. But the late Galician version of the Canzoniere presents the great merit of having created a lexical corpus that will be to a great extent the one that allows to emulate in Galician Petrarca’s pace, musicality and artifices. In this respect we echo the Theory of the Polysystems, which had indicated the importance of the literature translated in the conformation of literary systems, as translations determine actively the constitution of the above mentioned systems and can occupy its center in case of marginal or peripheral systems.
Keywords: Translation; Petrarca; Canzoniere; Galicia; polysystems